2018
DOI: 10.17116/flebo201812135-39
|View full text |Cite
|
Sign up to set email alerts
|

Endovenous Laser Ablation of the Great Saphenous Vein with Large Sapheno-Femoral Junction

Abstract: Эндовенозные лазерные и радиочастотные методы обладают большой доказательной базой и рассматриваются как методы выбора для устранения рефлюкса по магистральным подкожным венам у

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…3,11,15 Three studies reported on EHIT occurrence with crude and pooled outcomes of 1.7% (8/465) and 1.6% (95% CI: 0.3–3.5) ( I 2 = 0%, p = 0.72). 14,16,17 Out of the three included studies, two provided further information regarding EHIT classification with one recorded EHIT III and three EHIT II incidents.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3,11,15 Three studies reported on EHIT occurrence with crude and pooled outcomes of 1.7% (8/465) and 1.6% (95% CI: 0.3–3.5) ( I 2 = 0%, p = 0.72). 14,16,17 Out of the three included studies, two provided further information regarding EHIT classification with one recorded EHIT III and three EHIT II incidents.…”
Section: Resultsmentioning
confidence: 99%
“…The crude and pooled technical success estimates were 99.5% (630/633) and 99.9% (95% CI: 98.9–100.0) ( I 2 = 55%, p = 0.15). 11,13,14,16,17 Three studies reported on DVT occurrence. The crude and pooled DVT estimates were 0.3% (1/368) and 0.04% (95% CI: 0.0–3.4) ( I 2 = 25%, p = 0.26).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations